Pengaruh Bahan Pakan (Solid dan Pelepah Sawit Fermentasi) terhadap Bobot Lahir Pedet Sapi Bali - E. Ramon; Nurhaita Nurhaita; W. A. Wulandari; A. Ishak; Z. Efendi (Jurnal Peternakan, 2020)
The research was conducted in Sumber Arum Village, Seluma Regency from April to August 2018. The purpose of the study was to determine the effect of feed material (solid and fermented palm fronds) on female cows on the birth weight of calf Bali cattle. The material of the research was 7 months old pregnant cattles as many as 10 heads aged 2-4 years with initial Body Condition Score (BCS) of 3. Observations was conducted for 3 months with 1 month preliminary. The treatments used are: introductory treatment is forage 10% (palm fronds and leaves 12.5 kg/head/day, field grass 12.5 kg/head/day) + fermented solid 2 kg/head/day while the existing treatment is only given field grass as much as 10% of body weight + concentrate 2 kg/head/day. Each treatment consisted of 5 animals as replicates. The results of the analysis with the t test concluded that calf body weight at birth was not significantly different (P>0.05) between treatments.